Social and Humanitarian Cooperation: Experience and Prospects - V. A. Shamakhov (Евразийская интеграция: экономика, право, политика)
The article considers the main directions of social and humanitarian cooperation of the EEU member States, covering the fields of education, science, health, tourism and sports in order to improve the welfare and life quality of the Union countries' citizens. The goal is to create a single socio-humanitarian space that should not blindly reproduce the Western socio-humanitarian model of development based on the strategy of ”nurturing“ a loyal ”civil society“. Otherwise, there will be a discrepancy between the implementation of the goal of forming a single economic space and social and humanitarian programs imposed from the outside in the context of liberal democratic ideology, which are destructive for the peoples ofEurasia.